The Phenomenon of the Mosque as a Philosophical Space: Analytical Study of Participants of Ngaji Fisafat at Jenderal Sudirman Mosque, Yogyakarta - Rahmah, Neli (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article discusses the phenomenon of philosophical recitation at the Jenderal Sudirman Mosque, Yogyakarta. This research starts from the public's assumption that studying philosophy is complex; studying philosophy makes people not believe in the existence of God, and then it starts from the assumption that mosques are usually used as places of worship, carrying out religious rituals. However, it is different from the Jenderal Sudirman Mosque in Yogyakarta. This research is qualitative and field-based with an Edmund Husserl phenomenological approach. The results of this research show that the participants who took part in the Philosophy Qur’an were not only students or Muslims but also non-Muslims, and some participants were transgender. Not only that, the participants also came from various social backgrounds. The activity of reciting the philosophical Qur’an is also popular because of the presence of Fahruddin Faiz as an icon of the Qur’an of philosophy at the Jenderal Sudirman Mosque. This reciting of philosophy can change the participants' perspective on error and distance them from God because studying philosophy can make people closer to God.